2017
DOI: 10.1002/pbc.26637
|View full text |Cite
|
Sign up to set email alerts
|

Optimal radiotherapy target volumes in intracranial nongerminomatous germ cell tumors: Long‐term institutional experience with chemotherapy, surgery, and dose‐ and field‐adapted radiotherapy

Abstract: NGGCT patients continue to relapse beyond 5 years. Late ventricular relapse occurred even in patients without clear evidence of germinoma component. Elevated CSF-AFP at diagnosis is associated with poor DFS and risk for distant CNS relapse. Patients with residual radiographic disease after chemotherapy or residual malignant histologies after second-look surgery have inferior outcomes. Our data support consideration of treatment intensification for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…No distant failures were observed in these nine patients, compared to a 16% spinal failure rate in patients who did not receive CSI. In addition, the authors observed a trend toward late ventricular and spinal recurrences when local radiotherapy was employed . Similarly, half of the patients in our series treated with focal radiation alone developed recurrences, which may have been prevented with the more traditional approach of CSI.…”
Section: Discussionsupporting
confidence: 54%
“…No distant failures were observed in these nine patients, compared to a 16% spinal failure rate in patients who did not receive CSI. In addition, the authors observed a trend toward late ventricular and spinal recurrences when local radiotherapy was employed . Similarly, half of the patients in our series treated with focal radiation alone developed recurrences, which may have been prevented with the more traditional approach of CSI.…”
Section: Discussionsupporting
confidence: 54%
“…Moreover, with a median follow‐up of 5.1 years (range, 0.06 to 8.0 years), distant relapse was reported in only 4% of patients with the majority of reported recurrences occurring locally (10%). In multiple retrospective studies and a prospective trial with limited patient numbers, CSI reportedly had a positive and independent protective value in preventing distant relapse …”
Section: Radiation Therapymentioning
confidence: 99%
“…Regarding dose reduction of WVRT, it appears to be feasible as only a few relapses of NGGCT occur in the ventricles after focal RT, and most of them are attributed to the germinoma component. Breen et al (22) reported three patients with ventricular relapses, all with a germinoma component, and Murray et al (23) reported three out of five patients with a germinoma component and one with bHCG between 50-200 IU/ L, which would be considered a diagnosis of germinoma in our series. In a separate initiative from the recently initiated ACNS2021, which includes whole ventricular and spinal canal irradiation (WVSCI) for all patients, the plan for our next Brazilian protocol will be to assess alternative treatment intensification strategies while retaining WVRT for patients with localized tumors.…”
Section: Discussionmentioning
confidence: 48%
“…Breen et al. ( 22 ) reported three patients with ventricular relapses, all with a germinoma component, and Murray et al. ( 23 ) reported three out of five patients with a germinoma component and one with βHCG between 50-200 IU/L, which would be considered a diagnosis of germinoma in our series.…”
Section: Discussionmentioning
confidence: 51%